Karakteristik aliran laminar melewati profil persegi berdasarkan komputasi dengan skema central difference dan hybrid difference - Nurpatria, N. (Universitas Mataram, 2019)
The characteristics of two computational schemes, central difference scheme and the hybrid difference scheme, which using identical computing parameters is investigated. The test case employed is isothermal rectangular cylinder laminar cooling to represent two dimensional incompressible transient flow. Simulation results on the first one shows a relatively higher temperature distribution with an energy diffusion contour pattern more intense. Whereas with hybrid difference, temperature are lower in average. Moreover, temperature contour is more stable. Simulation with hybrid difference indicates more converget results based on criterion of flow pattern and accuracy ratio.